Dampak Objek Wisata Floating Market Lembang Terhadap Kesejahteraan Ekonomi Masyarakat - Rika Mutiara; Deden Sumpena; Ali Azis (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
This study aims to analyze Floating Market Lembang program and the impact on the economic welfare of the community. This research is a qualitative research that used descriptive method. This method is used to describe, analyze, and express the phenomenon that occur in the field. The results of this study showed that Floating Market Lembang did not have a special program to improve the economic welfare of surrounding community, but rather to provide the opportunities such as employment opportunities, entrepreneurial opportunities and PAD income from Lembang Village. Moreover, Floating Market Lembang gave the positive and negative impact to the economic welfare of the community. Positive impact is increasing the opportunities of employment, community income, and developing better infrastructure. In contrast, negative impact is the traffic jam and air pollution occured. In conclusion, Floating Market Lembang has an impact on the economic welfare of the people of Lembang Village.